EXPERIENCES OF CAREGIVERS OF STROKE PATIENTS IN LUSAKA, ZAMBIA - Khondowe, Oswell; Mpofu, Ratie; Rhoda, Anthea (Journal of Community and Health Sciences, 2020)
Introduction: Stroke is a major cause of death and most survivors are left with residual disability and are dependent on others for essential care. Objectives: The objective of the present study was to determine the experiences of informal caregivers of stroke patients receiving out-patient physiotherapy treatment at the University Teaching hospital in Lusaka, Zambia. Methods: Both quantitative and qualitative approaches were used to collect data in the present study. Participants: A convenient sample of 70 caregivers was selected for the quantitative part of the study while 10 caregivers were purposively selected for the in-depth qualitative interviews. Setting: Out-patients at the University Teaching Hospital (UTH) in Lusaka, Zambia Intervention: The Caregiver Strain Index was used to collect quantitative data and in-depth interviews provided the qualitative data. Results: The mean age of the participants was 37.6 years. The study sample consisted of more females (70%) than males (30%). Financial constraints, family adjustments and being overwhelmed by their care-giving role were the experiences mostly highlighted by the caregivers in this study Conclusion: Caregivers are important role players in the rehabilitation of stroke patients. It is therefore important that rehabilitation professionals are aware of the experiences of these caregivers so that their needs could also be addressed when managing the stroke patient